Radiovesicolomics-new approach in medical imaging - Stępień, Ewa Ł.; Rząca, Carina; Moskal, Paweł (Frontiers in Physiology, 2022)
This review introduce extracellular vesicles (EVs) to a molecular imaging field. The idea of modern analyses based on the use of omics studies, using high-throughput methods to characterize the molecular content of a single biological system, vesicolomics seems to be the new approach to collect molecular data about EV content, to find novel biomarkers or therapeutic targets. The use of various imaging techniques, including those based on radionuclides as positron emission tomography (PET) or single photon emission computed tomography (SPECT), combining molecular data on EVs, opens up the new space for radiovesicolomics—a new approach to be used in theranostics.